Pengaruh Media Audio Visual Terhadap Minat Belajar Siswa pada Mata Pelajaran Ilmu Pengetahuan Alam Kelas IV MIS-Al Ihsan - Saputri, Dessy Liana; Darwis, Umar (Indonesian Research Journal on Education, 2022)
This study aims to determine the effect of Audio Visual Media on Student Interest in NaturalScience Subjects for class IV MIS Al Ihsan. This study uses descriptive research with a quantitative approach. The population in this study were all fourth grade students of MIS Al Ihsan, the sample in this study amounted to 30 respondents. This study uses a saturated sample technique. Data collection techniques consist of observation and questionnaires. The data analysis technique used is the instrument test, namely the validity test and reliability test, as well as the analytical method consisting of a simple linear regression test, t test, and the coefficient of determination test. The results of this study obtained the equation Y = 25,911 + (0.678)X, where the Audio Visual variable has a significant influence on the variable interest in learning. Partial test results Audio Visual variables have a positive and significant effect on Learning Interest in Natural Science Subjects, where it is known that the tcount 10,085 > t table 2,048 and the significant value is 0.000 <0.05. The results of the coefficient of determination test show that the value of R square obtained is 0.784, meaning that the percentage of Audio Visual on Learning Interest is 78.4%, while the remaining 21.6% is influenced by other variables not examined by this study.